Pemberdayaan Ekonomi dan Penyuluhan Vaksin Covid-19 pada Kelompok Remaja Perempuan Yayasan Wakaf Hamalatul Quran di Banda Aceh: Economic Empowerment and Covid-19 Vaccine Education in Adolescent Group of Women Hamalatul Quran Wakf Foundation in Banda Aceh - Aulina Adamy; Nopa Arlianti; Menawati Menawati; Nova Khairunnisa; Putri Nabila; Anisha Sahfira Putri; Irhamni Irhamni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has harmed the economic sector. As many as 3.05 million workers in Indonesia have been affected by layoffs (PHK) due to the coronavirus in early 2020. This pandemic has made the lives of the Acehnese people even more difficult for certain groups. The worst impact of the pandemic occurred in the lower middle class and women, one of which was the youth in the Aceh Besar region. In the group of young women, family economic problems also overlap with health problems. So by providing capital assistance and training in making mask connectors to groups of young girls, it is hoped that they will not only help them face the current pandemic but also become a new, better source of income in the long term. This is accompanied by educational activities about the importance of implementing health protocols and the benefits of the Covid-19 vaccine. Two methods are used: the first is providing information about Covid-19, Health Protocols, and the benefits of the Covid-19 vaccine, and the second is providing skills to make mask connectors using beads. From the activities carried out, it was known that participants received accurate information about Covid-19, health protocols during a pandemic, and the benefits of the Covid-19 vaccine. Participants had a high enough enthusiasm for the training in making mask connectors. They wanted to develop further the skills built from the results of this community service and marketing methods in the field.